(3GdTehd GdeGdj hOhQg aj JMbjb GdJfejI GdEbJUGOjI (B:s (3feGPL OhdjI (B/s - (3eMehO, eMeO NjQ GdOjfs ((3GdEScfOQjI (B: s (3OGQ GdJYdje GdLGeYj(B, s, 2019)
(3jgOa gPG GdcJGH Gdi GdJYQa Ydi GdTehd GdeGdj hOhQg aj JMbjb GdJfejI GdGbJUGOjI, MjK JMOK ef NdGd aUhdg Yf GdTehd GdeGdj hNWhGJ GdJecjf GdGbJUGOj , hYf COhGJg GdQFjSjI, ceG bOe feGPL Yf GdTehd GdeGdj ef GdOhd GdGSdGejI , HGddGVGaI Gdi JWHjbg aj OhdI eUQ(B.s
(3GdeQGLY U(B.210 (3agQS GdLOGhd U(B.225s
Keywords: (3GdJfejI GdEbJUGOjIs; (3GdTehd GdeGdjs